INFLUENCE OF PH ON THE INTERLAYER CATIONIC COMPOSITION AND HYDRATION STATE OF CA-MONTMORILLONITE: ANALYTICAL CHEMISTRY, CHEMICAL MODELLING AND XRD PROFILE MODELLING STUDY - Ferrage E.; Lanson B.; Tournassat C.; Rinnert E. (My University, 2005)
The hydration state of a <2 μm fraction of Ca-saturated SWy-2 montmorillonite was characterised after rapid equilibration (3 hours) under pH-controlled conditions (0.1–12.6 pH range). The solution composition was monitored together with the interlayer composition and X-ray diffraction (XRD) patterns were recorded on oriented preparations. Experimental XRD patterns were then fitted using a trial-and-error procedure to quantify the relative proportions of layers with different hydration states.The montmorillonite is mostly bi-hydrated in basic and near-neutral conditions whereas it is mostly mono-hydrated at low pH. The transition from the bi-hydrated to the mono-hydrated state occurs through very heterogeneous structures. However, the proportion of the different layer types determined from XRD profile modelling and that derived from chemical modelling using Phreeqc2 code strictly coincide. This correlation shows that the hydration modification is induced by a H3O+-for-Ca2+ exchange at low pH, the two species being distributed in different interlayers. This layer-by-layer exchange process occurs randomly in the layer stack.Under alkaline conditions, results from XRD profile modelling and from near infrared diffuse reflectance spectroscopy (NIR-DRS) clearly demonstrate that there is no CaOH+-for-Ca2+ exchange at high pH. The apparent increase in Ca sorption in smectite interlayers with increasing pH is thus probably related to the precipitation of Calcium-Silicate-Hydrate (CSH) phases, which also accounts for the decrease in Si concentration under high-pH conditions. This precipitation is thermodynamically favoured.
Keywords: montmorillonite